The Effect Of Woolwich Massage On Breast Milk Production In Primiparous Postpartum Mothers In The UPTD Gunung Sari Health Center Area, Ulu Belu District, Tanggamus Regency - Misfa Setiyawati; Nopi Anggista Putri; Hellen Febriyanti; Maulia Isnaini (Sean Institute, 2024)
In Indonesia in 2022, the achievement indicator for infants under 6 months receiving exclusive breastfeeding was 67.96%. However, this figure has not reached the National target of 80%. Low breast milk production or insufficient breast milk is the main reason mothers stop exclusively breastfeeding their babies. Low breast milk production is a condition where breast milk does not come out or very little milk production is released. Low milk production can be increased by performing Woolwich massage, which is massage performed on the lactiferous sinus area specifically 1-1.5 cm above the areola mammae to stimulate prolactin hormone. The purpose of this study was to determine the effect of Woolwich massage on increasing breast milk production in primiparous postpartum mothers. The research method was pre-experimental with a one-group pre-posttest design approach. The population in this study was 34 primiparous postpartum mothers. The sampling technique was purposive sampling, with a total sample of 30 primiparous postpartum mothers. This research was conducted in the Ulu Belu Health Center Area, Ulu Belu District, Tanggamus Regency in 2024. Data analysis used the Wilcoxon test. The research results showed the average breast milk production flow was 54.67 (less smooth) and after was 76 (smooth), with a p-value of 0.000 (<0.05) meaning there is an effect of Woolwich massage on increasing breast milk production in primiparous postpartum mothers. The suggestion in this research is that postpartum mothers can perform Woolwich massage independently to help smooth breast milk production so they can meet breast milk needs for babies to achieve exclusive breastfeeding.